Induction of micronucleus and nuclear alterations in fish (Oreochromis niloticus) by a petroleum - Hoshina, Marcia M. [UNESP]; de Angelis, Dejanira de Franceschi [UNESP]; Marin-Morales, Maria A. [UNESP] (Elsevier B.V., 2008)
In this study, micronucleus and nuclear alterations tests were performed on erythrocytes of Oreochromis niloticus (Perciformes, Cichlidae) in order to evaluate the water quality of the Atibaia river, in an area that receives effluents discharge of a petroleum refinery and also to evaluate the effectiveness of the treatments used by the refinery. Water samples were collected in five different sites related with a refinery from São Paulo State, Brazil. For the micronucleus and nuclear alterations tests, O. niloticus specimens were exposed for 72 h to the water samples and in pure ground water (negative control). The results herein obtained indicated that the treatments used by the refinery diminished the cytogenetic damage; however they were not fully effective, since the final mill has induced damages in the genetic material of the test organism. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Micronucleus; Nuclear alterations; Oreochromis niloticus; Refinery effluents